Collostructional transfer effects in Turkish learners of English - Gedik, Tan Arda (Pedagogical Linguistics, 2023)
Second language acquisition studies have mainly considered transfer between two or more languages as a binary setting, it either happens or does not. However, research emerging out of usage-based approaches show that such transfer effects might be more gradient than ever thought before (e.g., Goschler & Stefanowitsch, 2019 ). Investigating a construction that has been reported to pose problems such as overpassivization to L2 English learners, i.e., unaccusatives, this study aims to trace gradient transfer effects between Turkish and English in the intransitive-unaccusative construction in Turkish learners of English. Following Goschler and Stefanowitsch’s (2019) method to analyze, extract experimental items from English and Turkish corpora, and experiment with collostructional transfer effects, the study revealed similar findings. Findings suggest that learners are likely to transfer strongly entrenched L1 items into the L2 even at advanced proficiency levels. Interestingly, when the item is weakly entrenched in L1, speakers attune to the input in L2 with growing proficiency. Furthermore, proficiency or experience helps with preempting non-optimal constructional combinations. Pedagogically, the study suggests that collo-profiles may help teachers and students with mitigating unconventional item-construction combinations at advanced levels.<br
Keywords: construction grammar; collostructions; Turkish; transfer effects; unaccusative